2018
DOI: 10.3390/nu10101391
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coffee, Wine, and Chocolate Consumption on Cognitive Outcome and MRI Parameters in Old Age

Abstract: Coffee, wine and chocolate are three frequently consumed substances with a significant impact on cognition. In order to define the structural and cerebral blood flow correlates of self-reported consumption of coffee, wine and chocolate in old age, we assessed cognition and brain MRI measures in 145 community-based elderly individuals with preserved cognition (69 to 86 years). Based on two neuropsychological assessments during a 3-year follow-up, individuals were classified into stable-stable (52 sCON), interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 69 publications
6
53
1
3
Order By: Relevance
“…Our finding about coffee consumption was partially consistent with the findings from some previous studies [11][12][13]20,51]. A population-based study of 145 community-based older individuals [11] found a positive effect of coffee on cognitive performance. In addition, a recent 30-year follow-up study of 8000 Japanese-American men [12] suggested that coffee intake might protect against Parkinson's disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding about coffee consumption was partially consistent with the findings from some previous studies [11][12][13]20,51]. A population-based study of 145 community-based older individuals [11] found a positive effect of coffee on cognitive performance. In addition, a recent 30-year follow-up study of 8000 Japanese-American men [12] suggested that coffee intake might protect against Parkinson's disease.…”
Section: Discussionsupporting
confidence: 92%
“…A number of epidemiological studies have demonstrated an association between higher coffee consumption and better cognitive performance [9][10][11][12][13]. Cognitive benefits from coffee consumption were typically attributed to caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the risk of dementia was increased in people who abstained from alcohol in midlife or consumed >14 units/week. Furthermore, results from one MRI study [50] showed that wine consumption was related to less white matter lesions and better cerebral blood flow, demonstrating better cognitive function. Stampfer et al [51] published a cohort study examining the association between moderate alcohol intake and cognitive ability in women, concluding that less than one drink per day may be related to a lower risk of cognitive impairment.…”
Section: Evidence From Epidemiological Studiesmentioning
confidence: 99%
“…This positive association between the regular intake of moderate doses of coffee and the increased longevity and health quality with ageing is tightly related to the ability of coffee intake to decrease the risk of developing major age-releated chronic disorders, such as diabetes [ 175 , 176 , 177 , 178 , 179 , 180 ], cardiovascular diseases [ 150 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 ], stroke [ 189 , 190 , 191 , 192 ], depression and suicide [ 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 ], cognitive decline [ 202 , 203 , 204 , 205 , 206 , 207 ], and neurodegenerativce diseases, such as Alzheimer’s disease [ 208 , 209 , 210 , 211 , 212 ] and Parkinson’s disease [ 213 , 214 , 215 , 216 , 217 , 218 ].…”
Section: Other General Beneficial Health Effects Of Coffeementioning
confidence: 99%